Evidence-based interventions of dichotic listening training, compensatory strategies and combined therapies in managing pupils with auditory processing disorders (2017)
The need to develop a measure of managing children with a single profile of auditory processing disorders (APDs), and differentiate between true and artefactual improvements necessitated the study. The study also sought to determine the efficacy of interventions – both single and combined on APD, against no-treatment. Design: A randomised controlled trial of interventions (RCT) was adopted. Participants were randomly allocated to each of the intervention groups or the no intervention group. The 10 weeks intervention included 45 minutes three times a week therapeutic intervention on listening with noise and sound localisation ability in the home and school environments. Study sample: 80 pupils (7–11 years) with a single profile of APD participated in the study. Results: Treatments were effective on the cocktail party and sound localisation. The best result was realised with the combined therapy (CT), and there was no significant difference in performance in the remaining treatment groups. Conclusion: The intervention groups were beneficial to pupils with APD and should be adopted by clinicians.